Beyond belief : the American press and the coming of the Holocaust, 1933 - 1945 - Lipstadt, Deborah E., 1947- 1947- (Free Pr. u.a, 1986)
Examines the role of the American press in presenting the information known about the Jewish Holocaust during World War II to the American people in such a way that it fostered inaction and indifference.